Building Web Applications with UML Second Edition - Conallen, Jim (Addison-Wesley object technology series., 2002)
This is a new edition of the widely acclaimed Building Web Applications with UML . Based on the author's extensive experience as a Web developer, it incorporates helpful reader feedback, identifies and addresses modeling problems unique to page-based Web applications, and offers practical advice and straightforward solutions. This thoroughly revised Second Edition reflects the latest techniques and issues surrounding the development of software and systems for the Web. You will find: Updated, expanded examples and diagrams Enhanced coverage of the latest Web application security concerns Detailed coverage of proven object technology concepts as applied to the development of Web applications Robust, scalable, and feature-rich Web applications are attainable. Using the industry-standard Unified Modeling Language (UML) to create designs allows Web application developers to easily integrate them with other systems modeled in UML. Written for project managers, architects, analysts, designers, and implementers, Building Web Applications with UML, Second Edition , demystifies the challenging aspects of modeling with the Web Application Extension (WAE) for the Unified Modeling Language. Because UML has been widely accepted as the standard language for modeling software systems, it is without question the best option for modeling Web application designs. The WAE extends the UML notation with semantics and constructs that empower you to model Web-specific architectural elements using the Rational Unified Process or an alternative methodology. Furthermore, using UML allows the modeling of Web applications as a part of the complete system and the integration of the business logic that must be reflected in each application. With this book as your guide, you will be able to gain a clear understanding of how to address the unique problems of modeling the design of page-based Web applications, and more important, how to take your model directly into working code. 0201730383B08282002.